Benefit of achieving lactate clearance versus central venous oxygen saturation target as microcirculation end point resuscitation in severe sepsis and septic shock - Sinto, R; Suwarto, S; Lie, KC; Widodo, D; Pohan, HT (Critical care (London, England), 2014)
Keywords: Septic Shock, Severe Sepsis, Retrospective Cohort Study, Subject Group, Tissue Oxygenation